Peculiarities Of Emotional Of Children In Process Of Divorce Parents - Stepanyan, Narine; Avetisyan, Mariana; Nazaryan, Ani (Զանգակ հրատ.)
A significant place in the scientific literature is occupied by the study of the problem of the emotional state of children whose parents are in the process of divorce. The number of divorces has increased significantly in the last decade, which has a devastating effect on the mental inner world of children. Families that are in a difficult situation (divorce) feel lonely in the process of overcoming insurmountable problems. The article discusses the features of the emotional state of children in the process of divorce of parents, due to different age stages. They cannot realize the bad impact of the divorce process on the child. And the solution of one important problem remains unfinished: it is the restoration and preservation of the subtle inner world of the child in a chaotic situation. In this process, the child does not receive psychological support, protection, which leads to the fact that he is isolated from society, and considers himself the reason for the divorce of his parents. Intolerance and conflict between spouses are common features that exist in most divorces. Lack of mutual understanding, conflicts are often observed in the divorce process, which leads to the need for its implementation in court. Divorce of parents disrupts the process of further socio-psychological development of children. .
Keywords: Psychology